1990
DOI: 10.1016/0248-4900(90)90368-d
|View full text |Cite
|
Sign up to set email alerts
|

Secondary ion mass spectrometry analysis of the copper distribution in Drosophila melanogaster chronically intoxicated with Bordeaux mixture

Abstract: The fungicides used intensively in agriculture may affect non-target organisms. The concentrations of copper sulfate-based fungicide, Bordeaux mixture, normally used in agriculture, can significantly reduce both the life span and breeding rate of Drosophila melanogaster. The present study examines the distribution of copper in organ sections of fruit flies intoxicated with Bordeaux mixture, by secondary ion mass spectrometry. The organs of most control flies contained no copper. In contrast, copper accumulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Alternatively, Ctr1B might function within a copper detoxification organ in flies to internalize and therefore sequester excess copper. Early studies in flies demonstrated that the mesenteron and Malpighian tubule epithelial cells accumulate high levels of copper when flies were chronically intoxicated with the antifungal agent Bordeaux mixture, which contains high concentrations of CuSO 4 (52). It is also possible that, because we have shown that Ctr1B null larvae mount a weak transcriptional induction of the MtnA metallothionein, an important copper detoxification gene, this could lead to a copper toxicity phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Ctr1B might function within a copper detoxification organ in flies to internalize and therefore sequester excess copper. Early studies in flies demonstrated that the mesenteron and Malpighian tubule epithelial cells accumulate high levels of copper when flies were chronically intoxicated with the antifungal agent Bordeaux mixture, which contains high concentrations of CuSO 4 (52). It is also possible that, because we have shown that Ctr1B null larvae mount a weak transcriptional induction of the MtnA metallothionein, an important copper detoxification gene, this could lead to a copper toxicity phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…For example, metallothioneins are expressed in the "copper cells," which are well known for their peculiar ability to accumulate large amounts of copper (18,36; for a review, see reference 4). Cadmium was previously shown to accumulate in the anterior midgut, in the "iron cell" region, and in the posterior midgut in a pattern highly similar to the metallothionein induction we report here (33,37).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, metallothionein or MTF‐1 mutants are highly sensitive to elevated copper concentrations (Egli et al , 2006a). In Drosophila larvae, metallothionein expression and the sites of copper accumulation coincide, especially in the cytoplasm of so‐called copper cells of the midgut and also in the posterior midgut (Filshie et al , 1971; Tapp, 1975; Lauverjat et al , 1989; Marchal‐Segault et al , 1990; Egli et al , 2006a). Noteworthy, copper cells display a characteristic orange copper luminescence caused by a copper–metallothionein complex (Egli et al , 2006a).…”
Section: Introductionmentioning
confidence: 99%